KESENJANGAN DALAM PEMBANGUNAN EKONOMI ISLAM - Amila, Amila; Abidin, Muhamad Zainal (Institut Agama Islam Ngawi, 2024)
This research aims to reveal how inequality exists in developing countries, as well as government actions and Islamic views regarding the problem of inequality in economic development. The research method used a descriptive qualitative approach using primary and secondary data. The research results show that economic inequality is indicated by unequal growth in expenditure between community groups, while non-economic inequality is indicated by inequality in access to basic services, namely health, education, water and sanitation, and other basic services. The government played an active role by developing the economy in an inclusive manner, increasing worker-intensive investment, giving special attention to micro and small businesses, expanding the rural economy and developing the agricultural sector, guaranteeing social protection for all workers, continuing poverty reduction programs. In Islam, regarding the issue of inequality, there must be consistency in terms of economic growth and equality due to creating a fair situation.